Nutrient Digestibility of Cereal Grain Products and By-products in Extruded Diets for Nile Tilapia - Guimaraes, Igo G. [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Tachibana, Leonardo (Wiley-Blackwell Publishing, Inc, 2008)
Apparent digestibility coefficients (ADCs) provide estimates of nutrient availability in feedstuffs and can be used as a tool for selecting ingredients to compound cost-effective diets for fish. Extrusion process is one factor that could influence ADC values. Thus, a digestibility trial was undertaken to evaluate ADC of protein, energy, and dry matter, and apparent amino acid availability (AAAA) in five cereal grain products/by-products (corn, wheat middlings, broken rice, rice bran, and sorghum) in compounded diets for Nile tilapia. Chromic oxide was used as an external inert marker. The digestibility values of energy and dry matter in ingredients, in decreasing order, were highest for broken rice (95.34 and 96.45%), sorghum (82.37 and 87.29%), corn (67.34 and 82.21%), rice bran (57.58 and 55.59%), and wheat middlings (48.94 and 45.88%). Protein digestibility value was higher for corn (72.86%) and the lowest value was observed for sorghum (56.77%), while broken rice, wheat middlings, and rice bran presented values ranging from 63.01 to 66.88%. AAAA values were higher for corn (70.05%) and the lowest methionine and cystine availability values were recorded for wheat middlings and broken rice, respectively. Broken rice appears as one of the most indicated ingredient for using in Nile tilapia diets because of its highest values of nutrient digestibility when compared to the other energetic sources. The use of this information should aid more precise and economic diet formulation for Nile tilapia.